Effect of temperature on structural and optical properties of iron sulfide nanocrystals prepared from tris(N-methylbenzyldithiocarbamato) iron(III) complex. Issue 3 (7th July 2020) - Paca, Athandwe M.; Ajibade, Peter A.
Abstract: Tris( N -methylbenzyldithiocarbamato)iron(III) complex was used to prepare iron sulfide (FeS) nanocrystals, FeS1 at 120, FeS2 at 180 and FeS3 at 240 °C. P-XRD revealed that the nanocrystals FeS1 and FeS2 are in hexagonal pyrrhotite, Fe9 S10, crystalline phase whereas FeS3 nanocrystal is in pyrrhotite-6C, Fe11 S12, crystalline phase. TEM images showed nanocrystals with an average diameter of 5.42 and 25.07 nm for FeS1 and FeS2, respectively, while cluster of iron sulfide with an average particle size of 6.40 nm was obtained for FeS3 . The optical band gaps obtained from the Tauc plots are 3.90, 3.90 and 3.96 eV for FeS1, FeS2 and FeS3 nanocrystals, respectively, which indicate blue shifts ascribed to quantum confinement.